An integrated pedagogical model for swimming education: effects of problem-based, project-based, digital learning, and peer assessment - Ahmad; Riswanto, A Heri; Ismail, Agus; Junaidi; Dahlan, Firmansyah (Edu Sportivo: Indonesian Journal of Physical Education, 2025)
Background: Swimming instruction in higher education is still predominantly characterised by teacher-centred approaches, with limited empirical evidence examining the effectiveness of student-centred and integrated pedagogical models. In particular, little is known about the comparative impact of combining multiple learning approaches on swimming skill development across different swimming styles. Objectives: This study aimed to (i) examine the effects of an integrated learning (IL) model—combining problem-based learning (PBL), project-based learning (PjBL), digital learning media, and peer assessment—on students’ swimming learning outcomes across four swimming styles, and (ii) compare the effectiveness of the IL model with single PBL and PjBL approaches. Methods: A quasi-experimental pretest–posttest group design was employed involving 93 university students enrolled in a swimming course. Participants were assigned to three groups: IL, PBL, and PjBL. Data was analysed using paired-samples t-tests to examine within-group effects, two-way ANOVA to identify between-group differences, and Tukey HSD post hoc tests. Effect sizes and confidence intervals were also calculated. Finding/Results: The IL model produced significant improvements in swimming performance across butterfly, breaststroke, backstroke, and freestyle techniques, with large effect sizes observed in all styles. Comparative analyses revealed that the IL group achieved significantly higher learning outcomes than both the PBL and PjBL groups, while no significant difference was found between PBL and PjBL. Conclusion: The findings demonstrate that an integrated learning model that combines multiple student-centred pedagogical approaches, digital learning media, and peer assessment is more effective than single-method approaches in university-level swimming education. This model offers a promising pedagogical framework for enhancing swimming instruction and warrants further investigation across different educational levels and learning contexts.